Thermocatalytic decomposition of methane/methanol mixture for hydrogen production: Effect of nickel loadings on alumina support - Awad, A. (American Institute of Physics Inc., 2017)
Hydrogen produced by thermocatalytic decomposition of methane is termed as clean and alternative fuel however high reaction temperature and fast catalyst deactivation limitize the efficiency of this process. In this study nickel based catalyst supported on alumina with various Ni loadings were prepared by impregnation method and employed for TCD of methane/methanol mixture for hydrogen production. Surface area and pore volume were decreased by increasing the amount of nickel loading on alumina. The results revealed that both reaction temperature and nickel loading affected the reaction rates and catalyst deactivation time. Scanning electron microscope (SEM) and Thermogravematric analysis (TGA) were used for characterization of fresh and spent catalyst. Crystalline carbon was formed on the surface of the catalyst and was proved by TGA analysis. Methane yield increased as the reaction temperature was increased but the catalyst deactivation time was decreased as a lot carbon was encapsulated on the surface of the catalyst. © 2017 Author(s).